lncRNA NEAT1 promotes the proliferation and metastasis of hepatocellular carcinoma by regulating the FOXP3/PKM2 axis - Pan, Junping; Hu, Yingzhe; Yuan, Chenlu; Wu, Yafu; Zhu, Xinhua (Frontiers in Oncology, 2022)
Abstract Objective: Hepatocellular carcinoma (HCC) is a malignant tumors. The occurrence of HCC involves in the alteration of a variety of oncogenes or tumor suppressor genes, but the specific molecular mechanism remains unknown. This research prooved the effects of long non-coding RNA NEAT1 (LncRNA NEAT1) on the viability, proliferation, migration and invasion of hepatocellular carcinoma cells, and explored the mechanism behind these effects. Methods: NEAT1 in 97H and Huh7 cell lines were overexpressed or knocked down, respectively. The expression of FOXP3 and its target gene PKM2 was hinged on qRT-PCR and Western blot, respectively. RNA pull down and RNA Immunoprecipitation experiments were carried out to detect the interaction between NEAT1 and proteins. Finally, the effect of NEAT1 on the tumor volume of HCC was verified by animal experiments. Results: A series of experiments have shown that NEAT1 knockdown can inhibit the viability, proliferation, migration, and invasion of HCC cells, NEAT1 can bind FOXP3 to promote PKM2 transcription, PKM2 knockdown can inhibit the viability, proliferation, migration, and invasion of HCC cells, PKM2 knockdown reversed the function of NEAT1. Conclusion: LncRNA NEAT1 can promote the malignant behavior of HCC cells while silencing of NEAT1 inhibited that. Mechanically, NEAT1 promotes the transcriptional activation of PKM2 by binding FOXP3，PKM2 knockout reverses the function of NEAT1.